Benchmarking as a tool of management in the higher education system. (Journal of Educational Sciences, 2016)
Benchmarking is a research and introduction of the best of experience of competitors of organizations of other fields of activity. The benchmarking promotes increase of level of competitiveness of a higher educational institution, increase in profit, quality of provided educational services. The article is consideredthe role of benchmarking as tool of a control system in higher education institution. There reveals the concepts and types of a benchmarking, recommendations of practical application of a enchmarking.There is analysed a foreign experience of an innovative development of education. There also considered the main problems of facing higher educational institutions. Practical application of a benchmarking isdesignated in four consecutive actions, such as understanding of details of own management processes by educational, scientific and innovative activity of a higher educational institution, the analysis of activity ofothers of a higher educational institution, comparison of results of others of a higher educational institution with results of analyzed universities, introduction of necessary changes for separation reduction. All these actions result in productivity of all main processes of life cycle of educational services of a higher educational institution. Consideration of experience of foreign higher education institutions develops all stages of planning of processes of life cycle of educational services, and gives the chance to make the most effective solutions of various problems on improvement of a control system by quality of education of a higher educational institution. Ideology of a modern control system also are comprehensive fundamental rules of the management and management of process of continuous improvement of activity of the organization for satisfaction of requirements of all interested parties. On the basis of studying of advance of reforming of traditional higher education institutions the comparative analysis of the internal environment of higher education institution is provided. There is given the concept, that use in the mechanism of management of competitiveness of higher education institution of the concept of a benchmarking allows to introduce the best experience of conducting activity, to improve quality and management efficiency, to form the new concept of conducting educational process, to estimate professionalism of the management that finally leads to providing a sustainable development of educational institution and achievement of the set level of competitiveness.
Keywords: benchmarking; education system; modernization; foreign experience; innovative university; competitiveness